Gender-specific differences in the anthropometric characteristics of the distal femur and proximal tibia condyles - Marinković, Nadica; Aleksić, Ivan; Vasić Vilić, Jasenka; Janović, Nataša (Vojnosanitetski pregled, 2022)
Background/Aim. In the course of identification, skeletal remains are used to determine the gender, age, and height of the body. The pelvic bone, skull, and femur were commonly used to determine gender; however, modern radiology techniques have enabled the use of other bones of the skeletal system (all long bones, scapula, clavicle, metacarpal and metatarsal bones, vertebras, ribs, etc.). The aim of this study was to determine whether certain anthropometric characteristics of the distal femur and proximal tibia are indicative of gender differences. Methods. The respective research has been carried out between 2011 and 2014 at the Institute of Pathology and Forensic Medicine and Institute of Radiology of the Military Medical Academy in Belgrade on 203 subjects (152 men and 50 women), between 11 and 63 years of age (35.50 ± 12.98). Diagnostic magnetic resonance imaging (MRI) imaging of the living persons’ knees was used. Measures taken included the longest mediolateral diameter of the distal femur condyle, the mediolateral diameter of the proximal tibia condyle and the diameter of the proximal tibia intercondylar eminence. Descriptive statistics and the Student's t-test were used for statistical analyses of data. Results. The mediolateral diameter of the distal femur in men was from 7.70 cm to 9.70 cm (8.80 ± 0.39 cm), and in women from 6.60 cm to 8.50 cm (7.62 ± 0.39 cm). The mediolateral diameter of the proximal tibia in men was from 7.20 cm to 9.30 cm (8.09 ± 0.38 cm), and in women from 5.90 cm to 8.00 cm (7.04 ± 0.36 cm). The mediolateral diameter of the proximal tibia intercondylar eminence in men was from 1.00 cm to 2.30 cm (1.44 ± 0.21 cm), and in women from 0.90 cm to 2.00 cm (1.33 ± 0.21 cm). The measures obtained showed a gender-specific statistically significant difference. Conclusion. The mediolateral diameters of the distal femur condyle, proximal tibia condyle and proximal tibia intercondylar eminence are indicative of gender-specific differences and may be used in the procedure of determining gender based on skeletal remains.
Keywords: anthropometry; femur; sex factors; tibia